Natural oxygenation of Champagne wine during ageing on lees: A metabolomics picture of hormesis. (15th July 2016) - Roullier-Gall, Chloé; Witting, Michael; Moritz, Franco; Gil, Ryan B.; Goffette, Delphine; Valade, Michel; Schmitt-Kopplin, Philippe; Gougeon, Régis D.
Graphical abstract: Highlights: Very good repeatability of ultra-high resolution FTICR-MS. Metabolomics fingerprints of bottled wines are driven by vintage characteristics. Statistics revealed discriminant signatures for low and high oxygenated wines. Oxygenation mechanisms appeared to be different for low and high ingresses. Abstract: The oxygenation of Champagne wine after 4 and 6 years of aging on lees in bottle was investigated by FTICR-MS and UPLC–Q-TOF-MS. Three levels of permeability were considered for the stoppers, ranging from 0.2 to 1.8 mg/L/year of oxygen transfer rate. Our results confirmed a good repeatability of ultra-high resolution FTICR-MS, both in terms of m/z and coefficient of variation of peak intensities among biological replicates. Vintages appeared to be the most discriminated features, and metabolite annotations suggested that the oldest wines (2006) were characterized by a higher sensitivity towards oxygenation. Within each vintage, the oxygenation mechanisms appeared to be different for low and high ingresses of oxygen, in agreement with the hormesis character of wine oxygenation. In the particular case of single variety wines and for a given level of stopper permeability, our results also showed that variety discrimination could be easily achieved among wines.